2007
DOI: 10.1590/s1413-86702007000300004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis C and B virus infection in patients with idiopathic dilated cardiomyopathy in Brazil: a pilot study

Abstract: The idiopathic dilated cardiomyopathy (IDMC) is a disease of the cardiac muscle characterized by systolic dilation and/or dysfunction of one or both ventricles, symptoms of congestive heart failure and risk of early death. Several studies in animal models and in humans have supported the hypothesis of the viral infection as initial event in the immunopathogenesis of the ventricular dilation. The objective of this study was to correlate the presence of hepatitis C virus chronic infection and idiopathic dilated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Other studies have suggested that HCY infection is frequently found in patients with dilated cardiomyopathy (1, 2). However, other studies were not able to find an association between HCY infection and dilated cardiomyopathy (14,15). In a retrospective study, it was shown that NTproBNP is a sensitive marker of myocardial injury in patients with HF from HCY myocarditis (4).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have suggested that HCY infection is frequently found in patients with dilated cardiomyopathy (1, 2). However, other studies were not able to find an association between HCY infection and dilated cardiomyopathy (14,15). In a retrospective study, it was shown that NTproBNP is a sensitive marker of myocardial injury in patients with HF from HCY myocarditis (4).…”
Section: Discussionmentioning
confidence: 99%
“…9 These figures were not reproduced in a multicenter study conducted in Italy, which found the presence of HCV-positive serology in 12 of 309 (3.9%) patients with DCM., 11 and in another study conducted in Brazil, which found only one case of HCV infection among 34 patients with DCM evaluated by a university hospital in Bahia. 12 The pathophysiology of DCM as a consequence of myocarditis due to hepatitis C virus could be explained by three mechanisms described below. The first was by direct action of the virus, reinforced by viral replication in the myocytes and by the fact that the HCV core protein could damage the structure of these cells.…”
Section: Dilated Cardiomyopathymentioning
confidence: 99%
“…A study was done in Italy reported a prevalence of hepatitis C antibodies in patients with cardiomyopathy to be 3.9%, [132]. A study from Brazil reported a prevalence of hepatitis C carrier state of 2.9% [133].…”
Section: Prevalencementioning
confidence: 99%